David du Plessis and the Assemblies of God : the struggle for the soul of a movement - Ziefle, Joshua R. (Leiden ; Boston : Brill, 2012)
In David du Plessis and the Assemblies of God Joshua R. Ziefle utilizes the stories of both ecumenical Pentecostal David du Plessis and the Assemblies of God to detail the complicated tensions that arose during the Charismatic Movement of the 1960s and 1970s.
Includes bibliographical references and index.
Master record variable field(s) change: 610
Keywords: Du Plessis, David; Assemblies of God -- History; Assemblies of God -- Clergy -- Biography; Du Plessis, David; Assemblies of God; Pentecostalism -- United States -- History -- 20th century; Pentecostal churches -- Clergy -- Biography; United States -- Church history -- 20th century; RELIGION -- Messianic Judaism; Clergy; Pentecostal churches -- Clergy; Pentecostalism; United States; 1900-1999; Electronic books; Biography; Church history; History